Electrochemical Bromination of Glycals - Luo, Zhao-Xiang; Liu, Miao; Li, Tian; Xiong, De-Cai; Ye, Xin-Shan (Frontiers in Chemistry, 2021)
Herein, the convenient one-step electrochemical bromination of glycals using Bu4NBr as the brominating source under metal-catalyst-free and oxidant-free reaction conditions was described. A series of 2-bromoglycals bearing different electron-withdrawing or electron-donating protective groups were successfully synthesized in moderate to excellent yields. The coupling of tri-O-benzyl-2-bromogalactal with phenylacetylene, potassium phenyltrifluoroborate, or a 6-OH acceptor was achieved to afford 2C-branched carbohydrates and disaccharides via Sonogashira coupling, Suzuki coupling, and Ferrier rearrangement reactions with high efficiency. The radical trapping and cyclic voltammetry experiments indicated that bromine radicals may be involved in the reaction process.